Mental retardation and fragil X syndrome - Aydin, Mustafa; Taşkin, Erdal; Özcan, Kenan; Kabakuş, Nimet; Özlü, Ferda (My University, 2006)
Fragile X syndrome is a genetic disorder with a semidominance of X chromosome due to mutation in fragile X mental retardation-1 gen (familial mental retardation-1 or FMR-1) which is characterized by learning, linguistic and memory problems due to temporal lobe dysfunction. Fragile X syndrome is the second common cause of mental retardation after Down syndrome. Fragile X syndrome constitues 1/3-1/4 of X linked mental retardation. Its incidence is 1/4000 in male, 1/6000 in female children. There is no difference between ethnic groups.
Mental retardasyon ve frajil X sendromu
Keywords: brain dysfunction; chromosome mutation; clinical feature; Down syndrome; fragile X syndrome; human; mental deficiency; morbidity; review; sex ratio; temporal lobe; X chromosome